LEGO-Lipophosphonoxins: A Novel Approach in Designing Membrane Targeting Antimicrobials - Do Pham, Duy Dinh; Mojr, Viktor; Helusová, Michaela; Mikušová, Gabriela; Pohl, Radek; Dávidová, Eva; Šanderová, Hana; Vítovská, Dragana; Bogdanová, Kateřina; Večeřová, Renata; Sedláková, Miroslava Htoutou; Fišer, Radovan; et al. (Journal of medicinal chemistry, 2022)
The alarming rise of bacterial antibiotic resistance requires the development of new compounds. Such compounds, lipophosphonoxins (LPPOs), were previously reported to be active against numerous bacterial species, but serum albumins abolished their activity. Here we describe the synthesis and evaluation of novel antibacterial compounds termed LEGO-LPPOs, loosely based on LPPOs, consisting of a central linker module with two attached connector modules on either side. The connector modules are then decorated with polar and hydrophobic modules. We performed an extensive structure-activity relationship study by varying the length of the linker and hydrophobic modules. The best compounds were active against both Gram-negative and Gram-positive species including multiresistant strains and persisters. LEGO-LPPOs act by first depleting the membrane potential and then creating pores in the cytoplasmic membrane. Importantly, their efficacy is not affected by the presence of serum albumins. Low cytotoxicity and low propensity for resistance development demonstrate their potential for therapeutic use.
Keywords: buněčná membrána; Gram-Positive Bacteria; grampozitivní bakterie; albuminy; Albumins; Cell Membrane; vztahy mezi strukturou a aktivitou; Anti-Bacterial Agents; mikrobiální testy citlivosti; Gram-Negative Bacteria; Microbial Sensitivity Tests; Structure-Activity Relationship; gramnegativní bakterie; antibakteriální látky